Biodegradable Poly(butylene succinate‐co‐terephthalate) Fibers Incorporated with Nanoparticles under High Drawing Temperatures for Enhanced Mechanical Properties. Issue 8 (3rd July 2019) - Gu, Jiayi; Wei, Xing; Hou, Xueni; Wei, Zhenzhen
Abstract: The performance of materials depends strongly on their microstructures which, in turn, are dependent on the processing parameters. In this work, the emerging and biodegradable poly(butylene succinate‐ co ‐terephthalate) (PBST) nanocomposites with different nanoparticles (NPs) are generated via in situ polymerization and the corresponding composite fibers are fabricated via melt‐spinning for the first time. The NPs play a role as nucleating agents and can increase the crystallization rate. The real‐time investigation of evolution of fibers during uniaxial stretching is carried out on synchrotron radiation small‐angle X‐ray scattering beamline integrated with a thermomechanical equipment, so as to identify the effects of drawing temperatures and NPs on lamellar structure. Both the existence of NPs and high drawing temperature are beneficial to the formation and perfection of new lamellae. Moreover, NPs and relatively high temperature can improve the break strength of PBST fibers by 10–20%, which is reasonable according to the findings in structure development. Furthermore, the method employed here for property improvement of PBST fibers sheds light on performance optimization of other polymers and fibers. Abstract : Poly(butylene succinate‐ co ‐terephthalate) (PBST) nanocomposite fibers with different nanoparticles (silica and attipulgite) are fabricated via a melt‐spinning technique for the first time. The effects of drawing temperature on the structural evolution of PBST and its nanocomposite fibers during stretching are investigated. The mechanical properties of PBST fibers are improved by the addition of nanoparticles and elevation of drawing temperature.